Posterolateral elbow impingement in professional boxers - Valkering, K. P.; van der Hoeven, H.; Pijnenburg, B. C. M. (The American Journal of Sports Medicine, 2008)
Background: Elbow injury is common in boxing, but it has not been reported in the literature. The onset is often a hyperextension trauma caused by a missed hit. Clinically the boxers complain of pain, stiffness, and an extension deficit.